Autophagy in sexual plant reproduction: new insights. (2nd August 2021) - Zhou, Xuemei; Zhao, Peng; Sun, Meng-Xiang
Abstract: Autophagy is a mechanism by which damaged or unwanted cells are degraded and their constituents recycled. Over the past decades, research focused on autophagy has expanded from yeast to mammals and plants, and the core machinery regulating autophagy appears to be conserved. In plants, autophagy has essential roles in responses to stressful conditions and also contributes to normal development, especially in the context of reproduction. Here, based on recent efforts to understand the roles and molecular mechanisms underlying autophagy, we highlight the specific roles of autophagy in plant reproduction and provide new insights for further studies. Abstract : Recent advances in the study of autophagy highlight its critical roles in sexual plant reproduction and several fundamental questions worthy of investigation in the future.